Preventing Human Trafficking in Global and Vietnamese Context - Le, Trung Kien (International Journal of Criminology and Sociology, 2019)
Crime prevention is an outreach measure to stop crime before it can occur. Prevention measures vary in different countries. In Vietnam, human trafficking prevention includes a range of strategies that are implemented by law enforcement agencies, other government agencies, social organisations, the media, community level organisations and individuals.In this paper, the author intends to exam the human trafficking situation and crime prevention in the world and Vietnam.